2010
DOI: 10.1534/genetics.110.118703
|View full text |Cite
|
Sign up to set email alerts
|

Control of Arabidopsis Leaf Morphogenesis Through Regulation of the YABBY and KNOX Families of Transcription Factors

Abstract: The patterning of initiating organs along specific axes of polarity is critical for the proper development of all higher organisms. Plant lateral organs, such as leaves, are derived from the shoot apical meristems located at the growing tips. After initiation, the leaf primordia of species such as Arabidopsis thaliana differentiate into a polarized structure consisting of a proximal petiole and a distal blade, but the molecular mechanisms that control proximal-distal pattern formation are poorly understood. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…The ankyrin repeat is a very common protein–protein interaction motif in nature and occurs in a large number of functionally diverse proteins. The results agree with previous studies that showed this gene interacts with other genes to control leaf and/or flower development 47–49…”
Section: Resultssupporting
confidence: 93%
“…The ankyrin repeat is a very common protein–protein interaction motif in nature and occurs in a large number of functionally diverse proteins. The results agree with previous studies that showed this gene interacts with other genes to control leaf and/or flower development 47–49…”
Section: Resultssupporting
confidence: 93%
“…Given that pan loss-of-function did not reproduce the RIM- phenotype (Figure 5a) other genes, perhaps TGAs , are involved in this phenotype, as shown for SA perception [23]. Given that BOPs play both positive and negative roles in transcriptional regulation of the KNOX (Knotted1-like homeobox) gene KNAT6 [46], we also tested if RIM was affected by knat6 loss-of-function, but again, no difference was observed (Figure 5a). This may reflect redundancy with other KNOX genes, or more likely, that BOP regulation of RIM is independent of KNAT6.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is the case for the C2H2 Zn-Finger encoding gene JAGGED (JAG; Dinneny et al, 2004;Ohno et al, 2004), and for the closely related YABBY1 (YAB1) group genes FILAMENTOUS FLOWER (FIL, Chen et al, 1999;Sawa et al, 1999) and YABBY3 (YAB3, Siegfried et al, 1999). These genes were identified initially for their roles in repressing meristematic activities in lateral organ primordia and for controlling abaxial-adaxial polarity of the leaf (Chen et al, 1999;Sawa et al, 1999;Siegfried et al, 1999;Kumaran et al, 2002;Dinneny et al, 2004;Ohno et al, 2004;Ha et al, 2010). Most recently, it has been proposed that along the medio-lateral axis of the ovary, JAG, FIL and YAB3 act redundantly in a gradient of activity (known as JAG/FIL activity) to promote valve and valve margin formation (Dinneny et al, 2005;Alonso-Cantabrana et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in the replum, RPL has been also shown to regulate meristem maintenance of the SAM by interacting genetically and molecularly with members of the class I KNOX, including BP and SHOOTMERISTEM-LESS (STM, Endrizzi et al, 1996;Long et al, 1996;Byrne et al, 2003;Smith and Hake, 2003;Bhatt et al, 2004;Smith et al, 2004;Cole et al, 2006;Kanrar et al, 2006;Scofield et al, 2007;Rutjens et al, 2009). However, members of the JAG/FIL activity act antagonistically to meristematic genes including BP (Kumaran et al, 2002;Ha et al, 2010). Similarly in the fruit, JAG/FIL genes negatively regulate the expression of RPL and BP (Dinneny et al, 2004;Alonso-Cantabrana et al, 2007).…”
Section: Introductionmentioning
confidence: 99%